Kosakata Bercocok Tanam Padi di Sawah pada Masyarakat Dayak Ketungau Sesat: Kajian Semantik Kultural - Pabianus Simon (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research focuses on the language that is suitable for planting rice in the rice fields of the Ketungau Sesat Dayak community. The method used in this research is descriptive. The data in this research is in the form of vocabulary suitable for planting rice in rice fields in the Ketungau Sesat Dayak language. Based on the results of the research conducted, the researchers succeeded in collecting 84 vocabularies consisting of 7 classifications. The data is based on 24 equipment or equipment classifications, 28 based on process classifications, 1 based on place name classifications, 13 based on rice growth classifications, 6 based on soil type classifications, based on the classification of results as many as 9, and based on the classification of signs as many as 3 vocabularies.